(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the effect of studied factors on the accumulation of dry matter in mungbean varieties in the conditions of marshy meadow soils is described, and the effect of sowing rates and periods was observed in the experiments. According to the results of the research, the acceptable norms and terms have been determined